2010
DOI: 10.1016/j.jconrel.2010.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of siRNA loaded dextran nanogel with blood cells

Abstract: Although the behavior of nanoscopic delivery systems in blood is an important parameter when contemplating their intravenous injection, this aspect is often poorly investigated when advancing from in vitro to in vivo experiments. In this paper, the behavior of siRNA loaded dextran nanogels in human plasma and blood is examined using fluorescence fluctuation spectroscopy, platelet aggregometry, flow cytometry and single particle tracking. Our results show that, in contrast to their negatively charged counterpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…However, the in vivo circulation time of DEX NGs is still needed to be prolonged before their adequate extravasation and accumulation in the tumor tissue. , This limitation can be improved by PEGylation of DEX NGs and/or adjustment of their surface charge. For example, 2-aminoethyl methacrylate (AEMA) is introduced onto DEX-HEMA NGs to get DEX-HEMA-TMAEMA NGs, which can be further conjugated with methoxypolyethylene glycol ( M w , 5000). The siRNA-loaded NGs are able to be efficiently taken up by HuH-7 human hepatoma cells to show significant gene silencing effect in the cells.…”
Section: Biodegradable Natural Polymer-based Ngs For Drug/nucleic Aci...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the in vivo circulation time of DEX NGs is still needed to be prolonged before their adequate extravasation and accumulation in the tumor tissue. , This limitation can be improved by PEGylation of DEX NGs and/or adjustment of their surface charge. For example, 2-aminoethyl methacrylate (AEMA) is introduced onto DEX-HEMA NGs to get DEX-HEMA-TMAEMA NGs, which can be further conjugated with methoxypolyethylene glycol ( M w , 5000). The siRNA-loaded NGs are able to be efficiently taken up by HuH-7 human hepatoma cells to show significant gene silencing effect in the cells.…”
Section: Biodegradable Natural Polymer-based Ngs For Drug/nucleic Aci...mentioning
confidence: 99%
“…Similar to conventional NPs, PEGylation of NGs is an effective approach to improving their PK and biodistribution, because PEG can provide good steric hindrance to prevent nonspecific protein interaction, thus reducing opsonization and uptake by the RES. ,, For example, after intravenous injection into SCC7 tumor xenograft mice (female BALB/C nude mice), PEGylated HA NGs achieve longer circulation time in the blood and more effective accumulation (up to 1.6-fold higher) at the tumor tissue than PEG free HA NGs. At the same time, PEGylation can effectively reduce the liver uptake of the NGs, which may reduce toxicity to the liver.…”
Section: Pharmacokinetics and Biodistribution Of Ngsmentioning
confidence: 99%
“…Naeye and coworkers used particle tracking to assess the stability and biodistribution of covalently cross-linked dextran nanogels (dex-NG) that can be loaded with siRNA via electrostatic interactions [24]. Previous work by this group demonstrated that addition of 5 kDa PEG to the surface of siRNA-loaded dex-NG reduced interactions with blood cells and prevented aggregation in human plasma [25]. Similarly, Naeye found that the PEGylated dex-NG were stable upon incubation in mouse blood and plasma, yet the clearance after IV administration of free siRNA, siRNA-loaded dex-NG, and PEGylated siRNA-loaded dex-NG were indistinguishable [24].…”
Section: The Utility Of Particle Tracking Analysis In Drug and Genmentioning
confidence: 99%
“…chemically cross-linked polymer network [ 10,11 ] provide a broad spectrum of biomedical applications for drug delivery, [12][13][14][15][16][17][18][19] medical diagnostics, [ 20 ] bioimaging, [ 1,[21][22][23][24][25][26][27] and tissue engineering. [28][29][30][31] Particularly, nanogels are attractive pharmaceutical carriers due to their properties of ease of synthesis, tunable formulation, and tailored functionalization.…”
Section: Young Talents In Polymer Sciencementioning
confidence: 99%
“…Nanogels, nanoscaled hydrogel particles composed of physically or chemically cross‐linked polymer network provide a broad spectrum of biomedical applications for drug delivery, medical diagnostics, bioimaging, and tissue engineering . Particularly, nanogels are attractive pharmaceutical carriers due to their properties of ease of synthesis, tunable formulation, and tailored functionalization .…”
Section: Introductionmentioning
confidence: 99%